ALLIUM CEPA L.nıń BİO-EKOLOGIYALÍQ ÓZGESHELIKLERI - Baltabaev, M.T.; Kalbaeva, S. (SCIENCE and SOCIETY, 2019)
The article contains scientific data on the botanical characteristics, chemical composition, medicinal properties and biological characteristics of the origin of common onions.